Changing Perspectives on HDL: From Simple Quantity Measurements to Functional Quality Assessment. (27th April 2021) - Thakkar, Himani; Vincent, Vinnyfred; Sen, Atanu; Singh, Archna; Roy, Ambuj
Abstract : High-density lipoprotein (HDL) comprises a heterogeneous group of particles differing in size, density, and composition. HDL cholesterol (HDL-C) levels have long been suggested to indicate cardiovascular risk, inferred from multiple epidemiological studies. The failure of HDL-C targeted interventions and genetic studies has raised doubts on the atheroprotective role of HDL-C. The current consensus is that HDL-C is neither a biomarker nor a causative agent of cardiovascular disorders. With better understanding of the complex nature of HDL which comprises a large number of proteins and lipids with unique functions, recent focus has shifted from HDL quantity to HDL quality in terms of atheroprotective functions. The current research is focused on developing laboratory assays to assess HDL functions for cardiovascular risk prediction. Also, HDL mimetics designed based on the key determinants of HDL functions are being investigated to modify cardiovascular risk. Improving HDL functions by altering its composition is the key area of future research in HDL biology to reduce cardiovascular risk.